EFEKTIFITAS TERAPI MANDI AIR HANGAT DENGAN LEMONGRASS OIL MASSAGE TERHADAP KUALITAS TIDUR LANSIA DI PANTI SOSIAL LANSIA BUDI AGUNG KUPANG - Maria Lusia Indrawati Lotu (Universitas Citra Bangsa, 2020)
ABSTRACT The old is someone whose age is over than 60 years, who also has problem because of the decrease of organ disfunction, pshycology, social, economy and environmentso they need a special medical treatment one if the effect of organ disfunction descrease on the old is sleeping problem. The aim of this research is to know how effective bathing treatment using warm water wth lemongrass oil massage on the old sleeping quality in Pati Sosial Penyantunan Lansia Budi Agung Kupang. This research methode is used with qualsy experiment and true group design, pre post test design, sample consists of 60 responden with total technique sampling instrument and the use og questioner evaluated with Wilcoxon. We also use bathing SOP and massage SOP. The result of research shows that medical bathing using warm water is effective to increase the sleeping quality of the old (ρ value = 0,46) and also lemongrass oil massage gives the same result. Conclusion warm bath therapy with lemongrass oil massage is more effective in improving the quality of sleep in the elderly seen from the significant value of 0,12 after of therapy compared to the control group with value of 0,73. The research result can be used as a good and beneficial information in helping the old to overcome sleeping problem on the old. Keywords: elderly, lemongrass oil massage, sleep quality, warm bath therapy